EMPOWERMENT THROUGH VIRTUAL REALITY: THE CAPABILITIES OF VIRTUAL ENVIRONMENTS IN INSPIRING EMPATHY, IMMERSION, AND EMPOWERMENT - Khatibi, Marjan (Proceeding of the International Conference on Arts and Humanities, 2023)
With the help of virtual reality (VR), users are able to experience an imaginary world they cannot experience in real life. This study examines the potential of immersive virtual environments to inspire empathy and personal empowerment, particularly regarding social issues. The design process is aided by data and information gathered through interviews and observation of project participants. This research projects include #EmpowermentThroughVR, which reflects on current issues such as the Afghanistan Crisis and the ongoing hardships women in the Middle East confront. Participants in VR simulations view occurrences from the perspective of the individual facing the hardship and are asked to consider its implications and ramifications. This study explores whether participants would remain silent or show empathy for the victims of the catastrophe. The findings demonstrate that people’s perceptions and information intake are influenced by their feelings of being present in a virtual space. A real-world experience cannot be compared to a VR experience, but a VR experience is psychologically more potent than a mediated experience. VR enables users to engage with imaginary objects they cannot see or even envision in the physical world. According to the findings, people can feel empowered and experience things in virtual worlds that they would feel uneasy doing in the real world. A set of standards should be followed in VR to produce more realistic experiences that inspire and evoke empathy.